Characterization of mortars on the facade of buildings in Gaza-Palestine using experimental techniques - de Azevedo, Afonso Rangel Garcez; Marvila, Markssuel Teixeira; Tayeh, Bassam; Souza, Jessica; Teixeira, Silvio Rainho [UNESP] (Springer Nature, 2022)
The characterization of mortars of facades of buildings located in the Gaza Strip is the main objective of this work. More specifically, the objective of this work is to provide a reliable source of data that allows the documentation of the construction systems used and that serves as a basis for future renovations and interventions in the buildings under study. Three buildings built at different times (Al-Ashi 1920 BC, Al-Ghussain 1865 BC and Al-Hato 1331 BC) were chosen, aiming to evaluate the evolution of the binders used in these buildings. The characterization was performed by chemical mineralogical analysis (XRF), X-ray diffraction spectroscopy (XDR) and Fourier transform infrared spectroscopy (FTIR). The results show that the construction of Al-Ashi consists of mortars made with a natural hydraulic binder obtained with limestone rich in aluminosilicates (clay) and activated by sodium from sea water. Consequently, as the main decomposition phenomena, saline efflorescence was observed. In the realization of the Al-Ghussain building, a natural hydraulic binder was used, made with limestone rock, volcanic ash as natural pozzolans and gypsum plaster to improve the plasticity and adhesion of the mortars. The main pathologies observed were stains and disaggregation, related to the formation of secondary ettringites and mechanical impacts. Finally, the Al-Hato building, built according to Ottoman architecture, features mortars made with natural hydraulic binders like Al-Ghussain and natural fibers. The main pathology is the excess of porous phase, due to the degradation of the natural fiber over time. Thus, it is concluded that the techniques used allow the identification of the main binders used in the production of the mortars under study.
Keywords: Characterization; Historic facade; Historic mortars; Palestine mortars; Pathology